(untitled) (Acta Scientiarum. Health Sciences, 2012)
The population of elderly and non-elderly users of a Basic Health Unit (UBS) was interviewed regarding the use of cardiovascular and anti-diabetic medications, as well as the adverse effects that were noted. Hypertension and diabetes mellitus are conditions involving complications and compromise the quality of life of patients. The objective was to build a profile of these users. The cross-sectional study was carried out on patients older than 18 years of age and users of cardiovascular or anti-diabetic drugs in Centro Social Urbano UBS, located in Londrina – PR, Brazil. The result revealed the following statistically significant variables: lower use of beta blockers (p = 0.012) and metformin (p = 0.05) among the elderly compared to the overall average, and higher acetylsalicylic acid (ASA) (p = 0.006) use in people over 64 years of age. Reported adverse symptoms were lower among those over 64 years old (p = 0.03). Angiotensin-converting enzyme (ACE) inhibitors are the most used (63.5%), followed by diuretics (54.9%) and beta-blockers (27.7%). Among diabetic patients, 23.2% were using biguanides and 15.9% sulfonylureas; only 6.6% were insulin-dependent. The conclusion is that drug therapies within the sample were mostly in accordance with current guidelines.